(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
Evidence is mounting that teacher questions can assist students in various purposes in the teaching-learning process (Blosser, 2006; Bond, 2007; Cotton, 2007). The teacher tends to deliver a simple to the complex level of question, for the discussion can run smoothly (Bloom’s taxonomy level, 1956). Despite this, a variety of good questions will not guarantee that the interactive classroom will be created, the teacher needs to employ rephrasing, redirecting, probing, and reinforcement in her questioning (Goodwin et al, 1992). However, practically, teachers ask a large number of questions, which somehow they fail in doing questioning strategies (Wragg and Brown, 2001:p.28). This conceptual article describes the teacher’s questioning strategies in facilitating students’ learning and promoting their thinking skills. It highlights the fact that a teacher who has initially lack the ability to teach higher thinking skills can make considerable progress in terms of applying her knowledge in the classroom (Zohar & Dori, 2011). This article ends by arguing for some changes that need to occur in effective classroom questioning, including the need to give a stronger description of the extent of the level of question and the questioning strategies, which the teacher employed.